The Role of Notaries/Land Deed Officials in Combating Money Laundering Crimes with the Know Your Customer Principle - Indrawati Utama, Putri; Tresno Novianto, Widodo; Purwadi, Hari (CV. Inara, 2024)
This research delves into the alarming intersection of notaries/land deed officials and money laundering crimes, highlighting the role of notarial services as potential facilitators in illicit financial activities. While notaries traditionally serve as impartial witnesses to document signings, their involvement in verifying transactions has increasingly attracted scrutiny due to the potential for abuse by money launderers. This study examines the vulnerabilities within the notarial system that may be exploited for money laundering purposes, including lax regulatory frameworks, inadequate due diligence practices, and the lack of standardized reporting mechanisms. The abstract also explores the challenges in detecting and preventing such illicit activities, emphasizing the need for enhanced regulatory oversight, improved training for notarial professionals, and increased collaboration between regulatory bodies, law enforcement, and the notarial community and also implementing the principle of know your customer. As the findings suggest, addressing these issues is crucial for safeguarding the integrity of notarial services and fortifying the global financial system against the insidious threat of money laundering.